SELEKSI (RECRUITMENT) CALON KARYAWAN TETAP PT. BANK BTPN SYARIAH, Tbk MENGGUNAKAN CRITERIUM DECISION PLUS 3.0 - MUHAMAD IRSAN (LPPM, 2016)
Needs demands for outsourced employees as permanent employees in the workplace PT. BTPN Syariah, then the PT. BTPN Bank Syariah held against outsourcing employee screening. The candidates were selected through a series of tests. While the criteria considered in the selection, namely: education, psychological value, interviews, old outsourcing and interesting. The method used in this paper is a Graded Method Analysis Process (Analytic Hierarchy Process - AHP). The analysis shows that the most influential factor is interesting, while the least impact factor is education. With the help of software Criterium Decision Plus 3.0, obtained by employees of outsourcing next may be filed as Permanent employees.Keywords: Analytic Hierarchy Process, the selection of permanent employees, Criterium Decision Plus 3.0.